Pressure-induced metallization of black arsenic. (20th September 2019) - Li, Ruiping; Han, Nannan; Cheng, Yingchun; Huang, Wei
Abstract: Black arsenic (bAs), a cousin of black phosphorus, has attracted increasing attention due to its excellent physical properties such as high carrier mobility and high on/off ratio, which provide new opportunities for future field-effect transistors and photodetectors. As a clear and powerful means, hydrostatic pressure is commonly used to tune the structure and electronic properties of materials. However, there have been few reports to date about bAs under pressure. In this work, a theoretical study is presented on the structure, stability, and electronic properties of bAs under high pressure. The calculation results show that bAs becomes unstable at pressures above 3 GPa. A transition from direct band gap to indirect band gap occurs at 1.2 GPa, and with a further increase of pressure, bAs undergoes a phase transition from semiconductor to metal at a critical pressure of 2.2 GPa. In addition, the carrier effective masses can be modulated slightly by hydrostatic pressure.